PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT BHUMYAMCA SEKAWAN JAKARTA - Kunto Atmojo; Muhammad Amirrulloh (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
This study aims to determine the effect of work discipline on the performance of employees of PT Bhumyamca Sekawan Jakarta, the variable studied is work discipline on employee performance. This research uses descriptive research method with quantitative approach. Data collection techniques by distributing questionnaires to 140 employees. The results of the study showed a significant influence of work discipline on the performance of theemployees of PT Bhumyamca Sekawan Jakarta. Based on the results of the hypothesis testing the work discipline variable (X) to the employee performance variable (Y), the results of this study obtained the value of t arithmetic (22,935) ttable (1,665) then it can be concluded that Ho is rejected and Ha is accepted, meaning Work discipline (X ) partially significant effect on employee performance (Y). The results of linear regression analysis obtained the value of the linear regression equation Y = 7.354 + 0.890 X The constant value of 7.354 states that if the independent variable (X) = 0 then the dependent variable (Y) is 7.354. Work Discipline regression coefficient (X) of 0.890 which means that the addition or increase (X) of 1 unit will increase Employee Performance (Y) of 0.890. R Square value (Determination Coefficient) obtained by 0.792, which means the influence of work Discipline variable (X) on Employee Performance (Y) of 79.2%. The remaining 20.8% is influenced by other factors.